MEDIASI MENURUT PERATURAN MAHKAMAH AGUNG REPUBLIK INDONESIA NOMOR 1 TAHUN 2008 TENTANG PROSEDUR MEDIASI DI PENGADILAN - Abdul Rokhim (Masalah-Masalah Hukum, 2014)
Regulation of Appellate Court (PERMA) No. 1 Year 2008 containing comand to execute mediasi to each; every civil dispute before the case in checking by Ceremony Judge. Mediasi represent negiation process trouble-shooting the parties which is have dispute to which in assisting by a mediator. Function of Mediator to assist them in finishing problems among them by way of accommodating importance among both parties even though result of agreemnt of the parties which in assisting by mediator have the character of final and fasten the parties, to be target of Appellate Court to create Ground jurisdiction quickly is, simple and light expense have fufilled